Opredelenie kontsentratsii obshchego kaltsiya v krovi kak potentsialnogo markera sostoyaniya peretrenirovannosti - Belyaev, N. G. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The huge on the volume and the intensity of training load in modern sports is frequently the reason of the lack of adaptive potential of an organism and the development of the condition for the disadaptation - hypertraining. The author believes, that one of such markers of hypertraining can be the changes of the concentration of calcium (??) in the plasma of blood. This element, earlier considered only by the way of the realization of the basic function of the skeleton and curtailing of blood, appeared by the important component of course practically all the processes of an organism. The aim of this study was to substantiate or to refuse that hypothesis. The researches were carried out on laboratory animals - rats. The condition of hypertraining was modeled in animals preliminary adapted to physical loads according to tasks of work. The training of animals was carried out on tredban. The condition of hypertraining was formed after the expiration of 8 weeks of the training microcycle by the daily increase of the intensity and the duration of loads. The process of adaptation of an organism to the action of repeatedly repeating irritants - the physical loads lays in the basis of hypertraining development. Not only physical serviceability rises in the result of it, but also forms the certain morphofunctional status of an organism. The long activation of an organism will be accompanied by the development of the condition of disadaptation - hypertraining. The strongly pronounced hypercalcemia during long and intensive training loads can be considered as occurrence of initial or latent, and hypocalcemia - the generated stage of disadaptation.